PENERAPAN SISTEM PAKAR BERBASIS WEB UNTUK DIAGNOSA PENYAKIT PADA IKAN LELE - Gregorius Teheq Buyanaya, Gregorius Teheq Buyanaya; Sitohang, Sunarsan (Computer Science and Industrial Engineering, 2022)
Freshwater fish cultivating business is one piece of the many types of business that open entryways with exceptionally enormous benefits where, this improvement is a method for raising and duplicate fish, and afterward the outcomes are gathered and sold or drank. The motivation behind this examination is to plan an electronic master framework in diagnosing catfish illness and the advantages of this exploration can add knowledge to the local area, particularly catfish ranchers, about how to develop catfish appropriately and accurately. This fish likewise catfish is a fish with various degrees of purpose, the review expressed that this fish is a side dish with the primary degree of purpose when contrasted with different sorts of side dishes. The strategy utilized in this examination is forward directing, which is a procedure to find or make ends in light of existing data or realities which then, at that point, prompts an end, then, at that point, attempted individually in an extraordinary condition. The aftereffect of this examination is to analyze sickness in catfish in light of the site utilizing HTML and PHP programming dialects. However, the plan utilized in this study has restrictions on issue ID, issue detailing, research targets for dissecting the information required, and delivering a specialist framework for diagnosing catfish illness in light of a site and ideally valuable for clients, specifically cultivators and conventional individuals.